2016
DOI: 10.1080/21645515.2016.1172758
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal pneumococcal carriage rates among HIV-infected adults following widespread pediatric use of conjugate pneumococcal vaccine-13

Abstract: Background: Nasopharyngeal pneumococcal carriage rates among HIV-infected adults has not been described since conjugate pneumococcal vaccine-13 (PCV13) was added to the universal infant and childhood vaccination schedule in 2010. Methods: HIV-infected adults presenting for routine health care visits to the Designated AIDS Center in Syracuse, NY between December 2013 and June 2015 were eligible for enrollment. Demographic, medical, and social history were recorded after obtaining informed consent. Nasopharyngea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…The pneumococcal colonization rate (13.47%) that we had observed is also comparable to the prevalence rates, 20% and 22.% respectively reported from Malawi and Indonesia [8,26]. However, it is higher than the 3% reported from the USA, 7.3% from Ghana, and 6.4% from Kenya [30][31][32]. At the same time, two studies reported a very high pneumococcal colonization rate ie., 43.2% and 34.6%, surprisingly both from Kenya [14,38].…”
Section: Nasopharyngeal Colonizationsupporting
confidence: 86%
See 1 more Smart Citation
“…The pneumococcal colonization rate (13.47%) that we had observed is also comparable to the prevalence rates, 20% and 22.% respectively reported from Malawi and Indonesia [8,26]. However, it is higher than the 3% reported from the USA, 7.3% from Ghana, and 6.4% from Kenya [30][31][32]. At the same time, two studies reported a very high pneumococcal colonization rate ie., 43.2% and 34.6%, surprisingly both from Kenya [14,38].…”
Section: Nasopharyngeal Colonizationsupporting
confidence: 86%
“…Secondly, nasopharyngeal pneumococcal colonization is an important reservoir and it acts as a marker for resistance among co-colonizing microflora in the upper respiratory tract of the host (e.g., H. influenzae and N. meningitides) [27][28][29]. Thirdly, a high prevalence of resistant pneumococci is identified by WHO as one of the most pressing issues [30][31][32][33]. Even conflicting reports on nasopharyngeal pneumococcal colonization are pouring in from different countries across the globe and will be elaborated later in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…While pneumococcal conjugate vaccines are safe and immunogenic in HIV-infected individuals, the generated antibody responses vary in functionality with ART and virologic control, tend to be less durable, and have lower efficacy in preventing invasive disease (37). Moreover, nonvaccine and nontypeable pneumococcal serotypes predominate in surveillance studies of pneumococcal carriage in HIV-infected individuals in areas of high PCV coverage (38,39), suggesting that the efficacy of PCV immunization in HIV-infected individuals may be further limited. Prior work from our group has demonstrated broad reactivity and serotype coverage of the antibody response elicited by WCV immunization in animals (40).…”
Section: Discussionmentioning
confidence: 99%